It is time to update the adjustment factors for age in Social Security retirement benefits - Mark J. Warshawsky (American Enterprise Institute (AEI), 2021)
There are adjustment factors for early and late claiming of retirement benefits in Social Security which depend on the age when benefits are claimed. These adjustment factors are seriously out of date, as both interest and mortality rates have declined since the rules were designed and put into place. Moreover, the rules are inconsistent among categories of beneficiaries — workers, spouses and widow(er)s — in terms of age ranges and fair adjustment factors. This paper calculates that, under current interest and mortality rates, the early retirement factors for workers should be about 16 percent higher than current factors; this change, reducing the early retirement penalty, would generally favor the poorer and minorities, who generally claim earlier and have higher than average mortality. Delayed retirement credits should be about six percent lower, disfavoring high income and educated workers, who generally claim late. The appropriate dynamic system for changing the adjustment factors annually is simulated here, using estimates of real interest rates from the historical record of 1919 to 2021. The results support a five- or ten-year moving average for continuous changes to the adjustment factors, to remove unusual volatility. Moreover, policy logic supports consistency in the factors across the beneficiary categories, as well as across age ranges — ages 62 to 72 is now an appropriate uniform age range, given current higher life expectancies and longer working lives.
Keywords: A; 330; Aging; Benefits; Retirees; Retirement; Social Security